2022
DOI: 10.3390/ani12040499
|View full text |Cite
|
Sign up to set email alerts
|

Eye Region Surface Temperature and Corticosterone Response to Acute Stress in a High-Arctic Seabird, the Little Auk

Abstract: Measuring changes in surface body temperature (specifically in eye-region) in vertebrates using infrared thermography is increasingly applied for detection of the stress reaction. Here we investigated the relationship between the eye-region temperature (TEYE; measured with infrared thermography), the corticosterone level in blood (CORT; stress indicator in birds), and some covariates (ambient temperature, humidity, and sex/body size) in a High-Arctic seabird, the Little Auk Alle alle. The birds responded to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Consistently, in closely related Emperor penguins ( Aptenodytes forsteri ), acute stress leads to an approximate 1.5°C increase in internal (stomach) temperature (Regel and Pütz, 1997). Such an increase in T eye in response to handling stress has been reported two times in avian species to the best of our knowledge (Ikkatai and Watanabe, 2015; Jakubas et al, 2022), while most previous studies have shown either a significant decrease (4 studies) or no significant change (4 studies; Table 1). Those contrasted findings might be explained by at least three factors: 1. variation in body size, since smaller individuals/species are expected to favour internal heat conservation by reducing more markedly peripheral blood flow and surface temperature compared to large ones ( thermoprotective hypothesis ; Robertson et al, 2020a); 2. differences in the thermal environment, since it has been shown that during acute stress response, heat conservation is favoured below the thermoneutral zone while heat dissipation is favoured above its upper limit (Robertson et al, 2020a); 3. the various delays at which T eye was measured in response to acute stress, since for instance the increase in T eye found by Ikkatai and Watanabe (2015) was short-lived (visible 5 min after the stressor, but not later on during the 30 min measurement period).…”
Section: Discussionmentioning
confidence: 69%
“…Consistently, in closely related Emperor penguins ( Aptenodytes forsteri ), acute stress leads to an approximate 1.5°C increase in internal (stomach) temperature (Regel and Pütz, 1997). Such an increase in T eye in response to handling stress has been reported two times in avian species to the best of our knowledge (Ikkatai and Watanabe, 2015; Jakubas et al, 2022), while most previous studies have shown either a significant decrease (4 studies) or no significant change (4 studies; Table 1). Those contrasted findings might be explained by at least three factors: 1. variation in body size, since smaller individuals/species are expected to favour internal heat conservation by reducing more markedly peripheral blood flow and surface temperature compared to large ones ( thermoprotective hypothesis ; Robertson et al, 2020a); 2. differences in the thermal environment, since it has been shown that during acute stress response, heat conservation is favoured below the thermoneutral zone while heat dissipation is favoured above its upper limit (Robertson et al, 2020a); 3. the various delays at which T eye was measured in response to acute stress, since for instance the increase in T eye found by Ikkatai and Watanabe (2015) was short-lived (visible 5 min after the stressor, but not later on during the 30 min measurement period).…”
Section: Discussionmentioning
confidence: 69%
“…That we did not detect sex differences in the relationship between sympathetic activation and T eye / T bill may relate to our relatively small sample sizes (male=9, female=8), and the fact that we only analysed the general relationship rather than response patterns. Studies reporting sex differences in body surface temperatures during acute stress have tended to be those using more animals and/or examining specific response features ( Blenkuš et al, 2022 ; Faraji and Metz, 2020 ; Knoch et al, 2022 ; Robertson et al, 2020a ; Wongsaengchan et al, 2023 ; although see Jakubas et al, 2022 ; MacRae et al, 2021 ; Ouyang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are encouraging signs that this is indeed the case, with increasing numbers of studies reporting characteristic body surface temperature changes during acute stress across a range of mammal (captive: Blenkuš et al, 2022 ; Faraji and Metz, 2020 ; Ludwig et al, 2007 ; MacRae et al, 2021 ; Riemer et al, 2016 ; Vianna and Carrive, 2005 ; Wongsaengchan et al, 2023 ; wild: Dezecache et al, 2017 ; Schraft and Clark, 2017 ) and bird species (captive: Edgar et al, 2011 , 2013a , b ; Giloh et al, 2012 ; Herborn et al, 2015 , 2018 ; Knoch et al, 2022 ; Moe et al, 2017 ; Ouyang et al, 2021 ; Robertson et al, 2020a , b ; Tabh et al, 2021 ; wild: Di Giovanni et al, 2022 ; Jakubas et al, 2022 ; Jerem et al, 2015 , 2019 ). However, there are two critical issues with this body of work.…”
Section: Introductionmentioning
confidence: 97%
“…To date, thermography has been used primarily on passerines. However, the thermal response of little auks to acute handling stress has been investigated (Jakubas et al, 2022), and although both plasma CORT and eye temperature increased in response to handling stress, there was no relationship between the magnitude of the responses of either variable. Further studies are needed to assess whether non‐invasive measures of body temperature can provide data on body condition in seabird species.…”
Section: Technology For Non‐invasive Ecophysiologymentioning
confidence: 99%
“…However, the thermal response of little auks to acute handling stress has been investigated (Jakubas et al, 2022) Establishing baseline reference values from 'healthy' wild populations is crucial for monitoring and assessing change under varying environmental conditions (Work, 1996;Newman, Piatt & White, 1997). Gathering these data will also assist captive rehabilitation of seabirds, by providing references for healthcare providers that are taxa, sex, and life-history-stage specific (Averbeck, 1992;Davey, Lill & Baldwin, 2000;Urvik et al, 2016).…”
Section: Faecal Glucocorticoid Metabolitesmentioning
confidence: 99%